2011
DOI: 10.1186/1471-2350-12-121
|View full text |Cite
|
Sign up to set email alerts
|

An entire exon 3 germ-line rearrangement in the BRCA2 gene: pathogenic relevance of exon 3 deletion in breast cancer predisposition

Abstract: BackgroundGerm-line mutations in the BRCA1 and BRCA2 genes are major contributors to hereditary breast/ovarian cancer. Large rearrangements are less frequent in the BRCA2 gene than in BRCA1. We report, here, the first total deletion of exon 3 in the BRCA2 gene that was detected during screening of 2058 index cases from breast/ovarian cancer families for BRCA2 large rearrangements. Deletion of exon 3, which is in phase, does not alter the reading frame. Low levels of alternative transcripts lacking exon 3 (Δ3 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 36 publications
4
23
0
Order By: Relevance
“…Previous results from our group showed that minigene tests of at least 16 different BRCA2 variants from exons 17 to 27 reproduced patient RNA outcomes . Moreover, the reproducibility of MGBR2_2–9 splicing outcomes was supported by previous studies based on patient RNA or minigene data, according to which fourteen variants matched preceding results: c.67+3A>G, c.68‐7T>A, c.316+3del, c.316+5G>C, c.426‐12_426‐8del, c.467A>G, c.516+ 1G>T, c.517G>T, c.572A>G, c.617C>G, c.627C>A/T, c.631G>A, c.631+3A>G and c.681+4A>G . Conversely, in a recent publication, variant c.68‐7T>A induced 20% of transcript Δ3 in lymphoblastoid cell lines of carrier patients versus 2.8% of Δ3 and 7.2% of Δ(6q 39 ,7) found in our minigene study in MCF‐7 cells .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Previous results from our group showed that minigene tests of at least 16 different BRCA2 variants from exons 17 to 27 reproduced patient RNA outcomes . Moreover, the reproducibility of MGBR2_2–9 splicing outcomes was supported by previous studies based on patient RNA or minigene data, according to which fourteen variants matched preceding results: c.67+3A>G, c.68‐7T>A, c.316+3del, c.316+5G>C, c.426‐12_426‐8del, c.467A>G, c.516+ 1G>T, c.517G>T, c.572A>G, c.617C>G, c.627C>A/T, c.631G>A, c.631+3A>G and c.681+4A>G . Conversely, in a recent publication, variant c.68‐7T>A induced 20% of transcript Δ3 in lymphoblastoid cell lines of carrier patients versus 2.8% of Δ3 and 7.2% of Δ(6q 39 ,7) found in our minigene study in MCF‐7 cells .…”
Section: Discussionsupporting
confidence: 75%
“…Hence, changes in this region may cause severe alterations in protein structure and functionality. Likewise, variants c.316+2T>C, c.316+3delA, c.316+5G>C and c.316+6T>C, which also induced Δ3, had been already catalogued as pathogenic . Consequently, all the Δ3‐inducing variants should be considered deleterious.…”
Section: Discussionmentioning
confidence: 99%
“…Several BRCA2 alterations causing the complete loss of exon 3 and the exclusive synthesis of ∆3 transcripts have been ascertained, including c.316 + 5G > C (Bonnet et al., ), c.316 + 3delA and c.68‐925_316 + 2889del (Muller et al., ) and c.156_157insAlu, a variant reported as a founder Portuguese mutation (Peixoto et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, using semiquantitative approaches, it has been documented that the variant leads to an increase of the naturally occurring transcripts lacking exon 3 (∆3) (Houdayer et al., ; Jarhelle, Riise Stensland, Maehle, & Van Ghelue, ; Sanz et al., ; Thery et al., ; Vreeswijk et al., ). A competitive quantitative PCR (qPCR) analysis estimated that the proportion of the ∆3 transcript compared to full length was approximately 25% in variant samples versus 4% in normal samples (Muller et al., ). More recently, segregation analyses in two families indicated that the variant did not segregate in the affected branches (Santos et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…LGRs fully characterized at the molecular level [4,6,9,[15][16][17][18][19][20][21][22][23][24]. Here, we describe the molecular characterization of four additional LGRs indentified in Spanish HBOC families.…”
Section: Introductionmentioning
confidence: 99%